2014
DOI: 10.2495/susi140401
|View full text |Cite
|
Sign up to set email alerts
|

Seismic performance of double-unit tunnel form building under in-plane lateral cyclic loading

Abstract: The seismic performance of one-third scale double units three-storey tunnel form reinforced concrete building tied up with foundation beam tested under in-plane lateral cyclic loading are performed and analysed in this paper. This building is designed according to BS 8110, constructed in heavy structural laboratory and tested under in-plane lateral cyclic loading using displacement control method. The specimen is tested on a strong floor starting from 0.01% drift until 1.25% drift with an increment of 0.25%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…During pushing in out-of-plane direction the spalling of concrete was observed at the upper parts of the joints and cracking of longitudinal reinforcement bar in the wall panel was occurring. The theoretical and experimental results compared and it indicates a good correlation between them Hamid, et al [44]. Hamid, et al [44] adopted the technique of repairing and strengthening for single unit three-storey tunnel form building which experienced under in-plane lateral cyclic loading.…”
Section: Review Of the Previous Studiesmentioning
confidence: 94%
“…During pushing in out-of-plane direction the spalling of concrete was observed at the upper parts of the joints and cracking of longitudinal reinforcement bar in the wall panel was occurring. The theoretical and experimental results compared and it indicates a good correlation between them Hamid, et al [44]. Hamid, et al [44] adopted the technique of repairing and strengthening for single unit three-storey tunnel form building which experienced under in-plane lateral cyclic loading.…”
Section: Review Of the Previous Studiesmentioning
confidence: 94%
“…Previous research had highlighted that most of the RC structures components which have been designed such as beam-column joint with corbel, wall-slab connection, tunnel form building and precast shear-key wall performed poorly under in-plane lateral cyclic loading [1,2,3,4]. In order to improve the performance of beam-column joint in RC moment-resisting frames, fuse-bars which acting as energy dissipater will be installed inside the beam-column joint.…”
Section: Findings From Previous Researchmentioning
confidence: 99%
“…Most of existing RC buildings in Malaysia were designed in accordance to British Standard (BS 8110) which did not have any provision and guidelines for earthquake loading at all. Experimental works had been conducted for tunnel form building [1], non-seismic precast RC beam-column joint [2], wall-slab joints of Industrialized Building System (IBS) [3] and precast shear-key wall panel [4] which designed according to BS8110. The experimental results showed that the structural components performed poorly under in-plane and out-of-plane loading with low ductility.…”
Section: Introductionmentioning
confidence: 99%
“…The 2015 Ranau earthquake is seen as an accelerating factor for implementation of seismic design for new buildings in Malaysia [7]. Hence, seismic design practice should be adopted especially in Sabah which is categorized as moderate seismic region in order to reduce the damage to buildings [8]. However, usage of construction materials due to seismic design consideration need to be investigated beforehand.…”
Section: Introductionmentioning
confidence: 99%